P57 To treat or not to treat. (23rd May 2012) - Thomas, J; Mathew, T; Carey, P B
Abstract : Background: The BASHH guidelines recommend offering full STI screening and epidemiological treatment to sexual contacts of those with confirmed Chlamydia infection. However, many patients attend sexual health clinics reporting to be contacts of Chamydia, but unable to give details of the index case. The management of these unverified Chlamydia contacts is unclear. Most clinics pragmatically treat contacts during their first visit; however some clinics may choose to wait for results before treating. This study was aimed at establishing current practice of management of Chlamydia contacts both verified and unverified, in a large inner city GUM clinic. Method: Health care practitioners were requested to fill in a questionnaire when patients who reported to be contacts of Chlamydia trachomatis attended the clinic over a 6-month period. Results: 59 Questionnaires were returned. In 76% (45/59) of patients attending as contacts of Chlamydia, details of index case could not be verified. 62% of these patients were asymptomatic and 56% (25/45) treated on first visit. Subsequently 27% (12/45) had a positive Chlamydia test whereas 36% of Chlamydia tests were positive in the cases where details of index case could be verified. The difference the positive rates of verified and unverified Chlamydia contacts is not significant (p=0.51). Conclusion: Despite acknowledging that our numbers are small, a high percentage of unverified Chlamydia contacts had positive Chlamydia tests. Given this we recommend that all patients attending STI clinics reporting to be contacts must be treated at first visit to avoid complications, losses to follow-up and decrease patient anxiety.